W roku 2008 o Tadeuszu Strumille (1880-1958) i Aleksandrze Kamińskim (1903-1978) w rocznicę Ich śmierci - Głowacka-Sobiech, Edyta (Biuletyn Historii Wychowania, 2008)
The article has a biographical and anniversary character. Its purpose is to recollect the profiles of two characters whose life and activity largely influenced the development of Polish education and the scouting movement: Tadeusz Strumiłło (1880-1958) and Aleksander Kamiński (1903-1978). In 2008 there occur the anniversaries of their death. Tadeusz Strumiłło became famous as a philosopher, promoter of alcohol abstinence, a scoutmaster of the internar period (among others, he was a chairman and vice-chairman of ZHP [Polish Scouts’ Association]). Aleksander Kaminski, in turn, is known as a writer, historian, founder of the cub scouting, co-founder of the Szare Szeregi (Grey Ranks - underground scouting association during World War II), initiator of Organizacja Małego Sabotażu (Organization of Small Sabotage) “Wawer” and the editor of “Biuletyn Informacyjny” (Information Bulletin), an outstanding social pedagogue of the 20th century.